Activation of the STING‐IRF3 pathway involved in psoriasis with diabetes mellitus. Issue 8 (17th February 2022) - Xiaohong, Li; Zhenting, Zhang; Yunjie, Yu; Wei, Cai; Xiangjin, Xu; Kun, Xie; Xin, Lin; Lu, Lin; Jun, Lu; Pin, Chen
Abstract: Psoriasis and type 2 diabetes mellitus (T2DM) share similar inflammatory pathways in their pathogenesis. The stimulator of interferon genes (STING)‐interferon regulatory factor 3 (IRF3) pathway has recently been shown to play an important role in immune and metabolic diseases. In this study, we investigated the activation of the STING‐IRF3 pathway in human immortalized keratinocytes (HaCaT) cells treated with palmitic acid (PA) and imiquimod (IMQ). Additionally, we detected the STING‐IRF3 pathway in diabetic mice with imiquimod (IMQ)‐induced psoriasis and assessed the potential of STING inhibitor C‐176. Furthermore, skin samples from patients with psoriasis and diabetes were collected for immunohistochemical analysis. The results indicated that the STING‐IRF3 pathway was activated in HaCaT cells. Moreover, the STING pathway was also found to be induced in the skin tissue of diabetic mice with psoriasis; the inflammatory responses were ameliorated by treatment with C‐176. In the skin tissue samples of patients with psoriasis and diabetes, immunohistochemistry showed that the expression levels of STING and phosphorylated IRF3 were also significantly increased. Thus, we conclude that the STING‐IRF3 pathway is involved in the inflammatory response in the manifestation of psoriasis with T2DM. Inhibition of the activation of the STING pathway can ameliorate the development of psoriasis in diabetes and could be targeted for the development of therapeutic agents for these conditions.